PENGARUH PROFITABILITAS, LEVERAGE, SIZE DAN KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN - Nandita, Asna; Kusumawati, Rita (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2018)
This study aims to analyze the effect of Profitabilitiy ,Leverage, Size and Dividend Polic on Firm Value. The object is manufacturing companies. The sample collection technique has been done by using purposive sampling. The samples are 23 companies which are listed in Indonesia Stock Exchange (BEI) and the research periods are five years which is started from 2012 to 2016. The analysis method has been done by using the multiple liniear regressions with Eviews Aplication. The result of this research shows that (1) profitability has positive influence to firm value; (2) leverage does not have any influence to the firm value; (3) firm size has positive influence to the firm value; (4)dividend policy has positive influence to the firm value.